2023
DOI: 10.1371/journal.pcbi.1011520
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic modelling of within-mosquito viral dynamics: Insights into infection and dissemination patterns

Jennifer S. Lord,
Michael B. Bonsall

Abstract: Vector or host competence can be defined as the ability of an individual to become infected and subsequently transmit a pathogen. Assays to measure competence play a key part in the assessment of the factors affecting mosquito-borne virus transmission and of potential pathogen-blocking control tools for these viruses. For mosquitoes, competence for arboviruses can be measured experimentally and results are usually analysed using standard statistical approaches. Here we develop a mechanistic approach to studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…aegypti mosquitoes with DENV. Despite being relatively simple, our model provides quantitative predictions which are consistent with our experimental data about how increasing the infection dose influences the rate at which mosquitoes become infectious—a phenomenon that has been demonstrated in previous experimental studies [ 21 , 22 ] and modelling work [ 29 ]. It also provides a framework that could be used to explore how perturbations to key mechanisms, for example, due to viral mutations or environmental fluctuations, may affect transmission rates.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…aegypti mosquitoes with DENV. Despite being relatively simple, our model provides quantitative predictions which are consistent with our experimental data about how increasing the infection dose influences the rate at which mosquitoes become infectious—a phenomenon that has been demonstrated in previous experimental studies [ 21 , 22 ] and modelling work [ 29 ]. It also provides a framework that could be used to explore how perturbations to key mechanisms, for example, due to viral mutations or environmental fluctuations, may affect transmission rates.…”
Section: Introductionsupporting
confidence: 84%
“…To account for this known characteristic, we used a phenomenological statistical model to allow specimens to remain uninfected. Others have shown that stochastic individual-based models of the invasion process can be used to understand the dose-dependency in the probability a mosquito becomes infected [ 29 ]; interestingly, this other work also hints at there being a strong dose-dependency in dissemination.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations